Gravity's rainbow - Pynchon, Thomas (New York : Penquin Books, 1995)
An American Lieutenant stationed in London during the Blitz has a bizarre ability.
Adult
Keywords: World War, 1939-1945 -- Aerial operations -- Fiction; Science fiction; World War, 1939-1945 -- Aerial operations -- Fiction; Europe -- History -- 1918-1945 -- Fiction; Europe -- History -- 1918-1945 -- Fiction